An Emerging Coinfection of Dengue and Scrub Typhus: A Hospital-based Study - Darshan Rakhecha; Bharat Umakant Patil; Mudita Nitin Joshi; Samir Yelwatkar (Wolters Kluwer Medknow Publications, 2024)
Background: Dengue fever and scrub typhus are endemic diseases in India. The aim was to study and compare clinical, biochemical, and hematological parameters between the dengue and dengue-scrub study groups. Materials and Methods: A retrospective hospital-based, cross-sectional study conducted at a tertiary care rural center. Various clinical, biochemical, and hematological parameters of dengue patients with random selection as the control group were compared with the dengue-scrub coinfection group (46 cases) as cases. The statistical significance was determined using an independent t-test. P < 0.05 was considered statistically significant. The t-test and the Mann-Whitney U-test were used. Results: Among the 86 cases (2.05%), scrub and dengue contributed 46 cases, followed by 27 cases of COVID-19 and dengue, four cases of malaria and scrub, three cases of malaria and dengue, and a single case of dengue with typhoid and leptospirosis with dengue. Serum albumin (P = 0.003, moderate effect size), serum globulin (P = 0.001, large effect size), alkaline phosphatase (P = 0.001, moderate effect size), and serum urea (P = 0.012, moderate effect size) levels were significantly different between only dengue and dengue-scrub group. In addition, the difference in hemoglobin levels, red blood cell count, white blood cell count, platelet count, cell variables, and ratios of those with dengue and scrub versus those with only dengue was significant (P < 0.05) with moderate-to-large effect size. Conclusion: Certain biochemical and hematological parameters such as albumin, globulin, alkaline phosphatase, platelet count, neutrophil-to-lymphocyte ratio, and platelet lymphocyte ratio can be used to support the diagnosis of coinfection (dengue-scrub).